(untitled) (Research, Society and Development, 2020)
This study used in a way connected to the hazop methodology, with the objective to analyze and identify risks, and its causes and consequences proposing improvements in one of the sectors of a beverage distributor, so, the activities developed in this sector were mapped and divided into the so-called study - nodes used to obtain better understanding and viabilization of the development of work, after the causes and consequences through the application of the brainstorming quality tool, in addition, the risks were qualitatively classified according to the method of the risk matrix. After the end of the study, the results appointed the human factor as responsible for the majority of deviations in the distributor and the factor training as a question to be improved, once it is necessary that many deviations are associated with the lack of training, that way, using the 5W1H quality tool, it developed an action plan for controlling risk levels.